Biodegradable implantable balloons: Mechanical stability under physiological conditions. (December 2019) - Haim Zada, Moran; Kumar, Awanish; Elmalak, Omar; Markovitz, Elana; Icekson, Ruthy; Machlev, Eli; Mechrez, Guy; Domb, Abraham J.
Abstract: Rotator cuff tendons injuries occurs as a result of trauma, e.g. due to falling, mechanical injuries and frequent overhead activity and as natural degenerative tears in elderly people. Biodegradable balloon shaped spacer of Poly-(L-lactide-co-ε-caprolactone) (PLCL) are applied in the treatment of these injuries. This type of treatment involves insertion of inflated biodegradable implant into the tissues of the damaged region in the shoulder to avoid shoulder impingement and reduce friction between the acromion and the humeral head and propagation of inflammation. The implant must maintain integrity under significant mechanical loading in order to remain effective. However, with time, the implant is exposed to the risk of failure due to the high pressure caused by the muscular motion and the friction with the bones. We report in this study the limits of the mechanical stability of the PLCL balloon shape spacer (implant) under prolonged cyclic loading, so as to be able to predict their physical stability in vivo . We have demonstrated in an in vitro settings that the implant withstands fatigue cycles for significantly longer than 8 weeks, which provides sufficient time window for patients to perform substantial rehabilitation and recover from an injury. The data presented herein is expected to assist medical practitioners in safety and efficacy measurements and assessment following spacer implantation.